The meeting as subjunctive form: public/private IT projects in British and Turkish state bureaucracies. (16th March 2017) - Alexander, Catherine
Abstract : Drawing on meetings within structured project environments in Turkey and Britain, this essay explores how and if this kind of highly rational, instrumental meeting travels and why so much frustration is typically expressed by British participants in such meetings. Meetings held in the Turkish senior government bureaucracy did not conform to expectation: they embraced formal and informal relations and were spectacles and tournaments of skill. I suggest that expectations of what constitutes a proper meeting are shaped by a specific British genealogy of common sense and technologies of fact creation, neither of which necessarily have purchase elsewhere. Nor is their applicability 'at home' straightforward, despite the fact that 'common sense' is often treated as simply commensurate with cultural systems as practical action: how one gets things done. Rather, the meeting, as shaped by this tradition, appears as a subjunctive form, a fiction of selective relationality where the meeting and project are treated as if they were set‐aside spaces, participants act as if they had single formal roles cut from a web of internal and external relations, and highly summarized information allows discussion towards a shared goal.